2022
DOI: 10.14814/phy2.15420
|View full text |Cite
|
Sign up to set email alerts
|

The moderate‐intensity continuous exercise maintains renal blood flow and does not impair the renal function

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Renal hemodynamics were assessed using the pulse Doppler method with a 3.5 MHz convex electronic scanning probe of an ultrasound system (Aplio 300; Toshiba Medical Systems) as described previously (Figure 2) (Kawakami et al, 2018(Kawakami et al, , 2022. First, the technician placed the probe on the left lumbar region of the participant in a seated position and drew the renal artery.…”
Section: The Assessment Of Renal Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal hemodynamics were assessed using the pulse Doppler method with a 3.5 MHz convex electronic scanning probe of an ultrasound system (Aplio 300; Toshiba Medical Systems) as described previously (Figure 2) (Kawakami et al, 2018(Kawakami et al, , 2022. First, the technician placed the probe on the left lumbar region of the participant in a seated position and drew the renal artery.…”
Section: The Assessment Of Renal Hemodynamicsmentioning
confidence: 99%
“…We evaluated changes in renal hemodynamics following exercise using ultrasound echo in previous studies (Kawakami et al, 2018(Kawakami et al, , 2022Kotoku et al, 2019). Renal hemodynamic assessment using ultrasound echo is non-invasive, can rapidly visualize blood vessels, and allows for repeated measurements over time that are less stressful to participants than the traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is with this background that we read with great interest the recent publication by Kawakami et al (2024) where it was reported that renal blood flow was maintained during high-intensity intermittent exercise (HIIE) and moderate-intensity continuous exercise (MICE), while concluding that "high-intensity exercise can be performed without a decrease in renal blood flow when performed intermittently for short periods." In their study, Kawakami et al employed Doppler ultrasonography to compare the renal hemodynamic responses to HIIE and MICE in 10 middle-aged male adults.…”
Section: E T T E R T O T H E E D I T O R Measuring Renal Hemodynamics...mentioning
confidence: 99%
“…However, in the recently published issue by Kawakami et al entitled “The moderate‐intensity continuous exercise maintains renal blood flow and does not impair the renal function,” the authors reported no change in renal blood flow in response to exercise in healthy middle‐aged men (Kawakami et al, 2022 ). Kawakami's findings are intriguing and challenge the current literature regarding blood flow response in the renal artery during exercise.…”
Section: Comment Lettermentioning
confidence: 99%